Job Satisfaction and the Healthcare Heroes: A Review - Santhi Raghavan; Ashwini M. Madawana (2021)
The global COVID-19 pandemic has pushed countries' health systems to breaking point, with previously unknown consequences for health professionals' job performance. While the COVID-19 pandemic has added stressors to healthcare workers' lives, it is unclear which factors will be the most valuable targets for interventions to reduce employee distress across the board. This article review compiles expressed thoughts on the multifactorial reasons for job satisfaction. The factors revolve around the scope of Burnout, Fear of Covid-19, Post Traumatic Stress Dysfunction (PTSD), lack of support and Resilience. It can be concluded that these scopes are interrelated and influence one's job satisfaction.